General practitioner perceptions and experiences of managing perinatal mental health: a scoping review - Jacqueline Frayne; Sarah Seddon; Tamara Lebedevs; Talila Milroy; Beverly Teh; Thinh Nguyen (BMC, 2023)
Abstract Background General Practitioners (GPs) are involved in preconception, pregnancy, and postnatal care. Overall, mental health remains a significant contributor to disease burden affecting 1 in 4 pregnant women. Psychotropic medication prescribing occurs in almost 1 in 12 pregnancies, and appears to be increasing, along with the prevalence of mental health disorders in women of reproductive age. Perinatal mental health management is therefore not an unlikely scenario within their clinical practice. This scoping review aims to map current research related to GPs perceptions and experiences of managing perinatal mental health. Method A comprehensive search strategy using nine electronic databases, and grey literature was undertaken between December 2021 and February 2023. Relevant studies were sourced from peer review databases using key terms related to perinatal mental health and general practitioners. Search results were screened on title, abstract and full text to assess those meeting inclusion criteria and relevance to the research question. Results After screening, 16 articles were included in the scoping review. The majority focused on perinatal depression. Findings support that GPs express confidence with diagnosing perinatal depression but report issues of stigma navigating a diagnosis. Over the last two decades, prescribing confidence in perinatal mental health remains variable with concerns for the safety profile of medication, low level of confidence in providing information and a strong reliance on personal experience. Despite the establishment of perinatal guidelines by countries, the utilisation of these and other existing resources by GPs appears from current literature to be infrequent. Many challenges exist for GPs around time pressures, a lack of information and resources, and difficulty accessing referral to services. Conclusion Recommendations following this scoping review include targeted perinatal education programs specific for GPs and embedded within training programs and the development of practice guidelines and resources specific to general practice that recognises time, services, and funding limitations. To achieve this future research is first needed on how guidelines and resources can be developed and best delivered to optimise GP engagement to improve knowledge and enhance patient care.